The importance of renewable gas in achieving carbon-neutrality: Insights from an energy system optimization model. (15th September 2022) - Shirizadeh, Behrang; Quirion, Philippe
Abstract: To address the cost-effective role of the different energy sources and carriers, energy optimization models should ideally consider the key energy supply, carrier, conversion, and storage options in an endogenous way, with high temporal resolution, and accounting for both positive and negative CO2 emissions. To do this, we develop a model optimizing dispatch and investment, meeting all the above-mentioned conditions, and we apply it to the French energy system for 2050 for a wide range of social cost of carbon (SCC) values (0 to €500/tCO2 ). Our findings show that (1) the optimal carbon-neutral energy system is highly electrified (∼80% of the primary energy supply), which implies highly electrified heating and transport sectors. (2) In the presence of renewable gas, a carbon-neutral energy sector can be achieved for a robust SCC of €300/tCO2 . (3) In such a system, renewables provide more than 90% of primary energy. (4) Therefore, renewables are crucial for achieving carbon-neutrality in a cost-effective way, and in the absence of renewable gas, carbon-neutrality cannot be achieved, even for an SCC of €500/tCO2 . Finally, (5) exclusion of nuclear energy from the energy system does not induce significant extra cost or emissions. Graphical abstract: Image 1 Highlights: We study the role of renewable gas in the future low-carbon French energy system. Renewable gas provides at least 20% of the primary energy. Renewables are the main enablers of carbon-neutrality (>90% of the primary energy). A high degree of electrification is required in the heat and transport sectors.